The national parks coast to coast : the 100 best hikes - Alvarez, Ted (Falcon Guides, 2016)
"Explore the crystal clear waters on the Summit Lakes Trail at Lassen Volcanic National Park, take in the expansive views at Shenandoah National Park's Old Rag Mountain, or traverse the sandstone cliffs at Angel's Landing in Zion National Park. Choose your adventure from any of the forty-four national parks profiled throughout the book. This book delivers jaw-dropping photos, detailed hike descriptions and maps, ranger essays, and more, all of which combine to create an intimate look at the best our national parks have to offer." --